A PROPOSED FORM FOR THE INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGIES WITH COST ACCOUNTING AND ADMINISTRATIVE ACCOUNTING SYSTEMS TO ENHANCE DECISION -MAKING EFFICIENCY IN THE DIGITAL BUSINESS ENVIRONMENT - Asst. Prof. Rasha Jasim Ahmed Ebraheem Alobaidy (Scholars Digest Publishing, 2025)
The research paper suggests a thorough method of deploying AI to combine cost accounting with the purpose of administrative accounting to make the business decision-making process efficient in the digital realm of business, namely, mid-to-large-sized corporations within the Iraqi economy. Such companies are supposed to have a manufacturing, service and financial aspect. The research questions to be addressed in the study include examining how AI can improve the quality, speed, and strategic value of accounting data that could help make more informed financial and administrative decisions. By identifying viable solutions to the areas of AI integration, the study will discuss the current issues related to the accounting processes and aims at developing a potent model that would enable organizations to apply AI to enhance the efficiency of the accounting processes and make the decision in the contemporary business context. The research surveyed about 90 accounting and finance professionals with experience in using AI-powered technology such as automated invoices, predictions, and AI-based reporting alongside their accounting systems based on a quantitative research design based on the Institutional Theory. The stratified sampling technique gave an array of views which included both the technical choices and the managerial outcomes in the Iraqi digital business climate. According to the results, the suggested type of AI integration influences the efficiency of the decision-making process greatly because it automates routine and repetitive accounting operations, delivers real-time, granular data in terms of costs and profitability, and improves the predictive power of analytics. These improvements enable organizations with the capacity to establish informed, data-driven decision making, predict market dynamics, and proactively address business issues among other things, adding to the strategic value of accounting in the digital transformation of business. The study recommends that companies in Iraq should choose more resources to the development of AI in order to modernize their accounting systems and provide instructional content that is targeted towards those to maximize the benefits of AI. It focuses on the crucial role of AI in improving the efficiency of competition in the business environment and decision making. involved in accounting in order
Keywords: Cost accounting, administrative accounting systems, AI technologies, digital business environment, decision -making efficiency.